Association between Neutrophil-Lymphocyte and Platelet-Lymphocyte Ratios and Coronary Artery Calcification Score among Asymptomatic Patients: Data from a Cross-Sectional Study - Carlos V. Serrano; Fernando R. de Mattos; Fábio G. Pitta; Cesar H. Nomura; James de Lemos; José Antonio F. Ramires; Roberto Kalil-Filho (Hindawi Limited, 2019)
Introduction. Atherosclerosis is a low-grade inflammatory disease. Among markers of inflammation, importance has been given to the neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR). The objective of this study was to examine the association between these hematological indices of inflammation and coronary atherosclerotic calcification in clinically asymptomatic patients. Methods. This study had clinical and laboratorial data collected from consecutive asymptomatic patients that underwent computed tomography coronary artery calcium (CAC) scoring. Risk factors, NLR, and PLR were evaluated at different categories of CAC scoring. Statistical tests included chi-square, linear regression, and logistic regression. Patients (N=247; age 60.4±8.0 years and 60.7% men) were allocated into four categories according to the CAC score. Results. Respective age, sex (male), NLR, and PLR distribution within groups were as follows: CAC=0 (n=98; 52.5±13.6 years, 55%, 2.0±1.0, and 121.5±41.5), CAC 1-100 (N=64; 61.3±11.0 years, 60%, 2.2±1.2, and 125.6 ± 45.6), CAC 101-400 (N=37; 64.2±11.6 years, 67%,2.6±1.3, and 125.4±55.9), and CAC>400 (N=48; 69.3±11.1 years, 66%, 3.3±2.0, and 430.1±1787.4). The association between risk factors and CAC score was assessed. Hypertension status and smoking status were similar within groups, while the presence of diabetes (P=0.02) and older age (P≤0.001) was more prevalent in the CAC>400 group. LDL cholesterol was greater in the higher CAC score groups (P=0.002). Multivariate logistic regression of the quartile analysis showed that age and NLR were independently associated with CAC>100 (OR (CI), P value): 2.06 (1.55-2.73, P=0.00001) and 1.82 (1.33-2.49, P=0.0002), respectively. Conclusion. Within asymptomatic patients, NLR provides additional risk stratification, as an independent association between NLR extent and CAD extent was identified. Moreover, PLR was not an inflammation marker for CAD severity.